Microencapsulated SAP modified low-carbon foam geopolymer and preparation method thereof

By microencapsulating the SAP, the water absorption and water release time is delayed, the problem of insufficient chemical durability and frost resistance of foamed polymers in engineering applications is solved, and the durability and performance of the material are improved.

CN119797819AInactive Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411769254.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In actual engineering applications, foamed polyscopy has problems such as poor chemical durability, poor frost resistance and greater self-shrinkage, which limits its widespread application.

Method used

SAP is microencapsulated by organic phase separation method, and cellulose derivatives are used as wall materials to wrap SAP particles, so that their water absorption and water release time is delayed, so that moisture is absorbed after the slurry is poured and water released after curing, reducing the impact on strength.

Benefits of technology

Without sacrificing fluidity and strength, the chemical durability and frost resistance of the foamed polymer are improved, and its self-shrinkage properties are enhanced, thereby enhancing the sound absorption and heat insulation properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797819A_ABST
    Figure CN119797819A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of novel inorganic nonmetal porous materials, in particular to a microencapsulated SAP (high-molecular water-absorbent resin) modified low-carbon foam geopolymer and a preparation method thereof. The preparation method is characterized in that an organic phase separation method is adopted to prepare a cellulose derivative wall material coated SAP microcapsule, and the microcapsule is added into foam geopolymer slurry to be uniformly mixed to prepare the modified low-carbon foam geopolymer. Microcapsule wrapping has the effect of delaying the water absorption-water release process of the SAP, and the problems that the fluidity of the SAP is reduced due to the fact that the SAP begins to absorb water when the foam geopolymer slurry is not poured and the strength is lost due to the fact that the SAP begins to release water when the slurry is not solidified are solved. The microencapsulated SAP modification can improve the strength (under the same density condition), chemical durability and freezing resistance of the foam geopolymer, improve the self-constriction of the foam geopolymer, and promote the development and application of the foam geopolymer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of novel inorganic non-metallic porous materials, in particular to a microencapsulated SAP-modified low-carbon foam geopolymer and a preparation method thereof. The material can be applied to the fields of roadbed filling, collapse treatment, impact protection, sound absorption and heat insulation, electromagnetic shielding, etc. Background Art

[0002] Geopolymer is a low CO2 emission aluminosilicate material that can be used to replace cement. It is formed by the polycondensation reaction of materials rich in silicon and aluminum under alkaline conditions. It has excellent properties such as early strength, heat resistance, and corrosion resistance. Making geopolymer into a porous structure can make it lightweight, heat-insulating, sound-insulating, wave-absorbing, and impact-resistant. However, foam geopolymer has problems such as poor chemical durability, poor frost resistance, and large self-shrinkage, which limits its application in actual engineering.

[0003] SAP is a highly water-absorbent material with a three-dimensional cross-linked network structure. It can absorb water up to 100 or even 1,000 times its own weight. It is biodegradable and environmentally friendly. When SAP is added to geopolymer, it can improve chemical durability, frost resistance, and improve self-shrinkage. However, due to the fast water absorption rate of SAP, the fluidity of the slurry will be significantly reduced after the addition of SAP, and the water-saturated SAP will gradually release water and leave holes under the action of osmotic pressure, causing the strength loss of the geopolymer around the SAP particles. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the above problems, the present invention provides a microencapsulated SAP modified low-carbon foam geopolymer and a preparation method thereof, which uses an organic phase separation method to microencapsulate SAP using a cellulose derivative as a wall material, so that its water absorption-release time is delayed as a whole, absorbs water in the geopolymer after the slurry is poured to prevent premature water absorption from affecting the fluidity during the slurry pouring, and releases water after the slurry is basically solidified to reduce the impact on the strength. Microencapsulated SAP modification can improve the chemical durability and frost resistance of the foam geopolymer without sacrificing fluidity and strength, improve the self-shrinkage of the foam geopolymer, and promote the development and application of foam geopolymer materials.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A microencapsulated SAP-modified low-carbon foam geopolymer and a preparation method thereof, comprising:

[0009] Step 1: adding cellulose derivative powder into an organic solvent and stirring at a certain temperature until the cellulose derivative powder is completely dissolved;

[0010] Step 2: Add SAP particles into the solution in step 1 and stir evenly;

[0011] Step 3: adding a non-solvent to the solution in step 2 and stirring, causing phase separation in the solution so that the cellulose derivative wraps around the SAP particles;

[0012] Step 4: After the solution in step 3 is cooled, the SAP particles are filtered out and placed in an oven to evaporate the solvent to obtain microencapsulated SAP;

[0013] Step 5: Mixing water glass and solid sodium hydroxide to prepare an alkali activator;

[0014] Step 6: Pour the foaming agent into the foaming pot and connect the air compressor to prepare the prefabricated foam by compressing air with the air compressor;

[0015] Step 7: Mixing the mineral raw material with the alkali activator described in step 5 to prepare a geopolymer slurry;

[0016] Step 8: adding the microencapsulated SAP in step 4 and the prefabricated foam in step 6 to the geopolymer slurry in step 7 and stirring evenly to obtain a microencapsulated SAP modified geopolymer slurry;

[0017] Step nine: placing the microencapsulated SAP modified low-carbon foamed geopolymer slurry in step nine into a silicone mold, curing it, and then demoulding it to obtain the final product.

[0018] The step one comprises:

[0019] The cellulose derivatives include methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, etc.

[0020] The organic solvent is an organic substance such as xylene, carbon tetrachloride, cyclohexane, etc. that can dissolve cellulose derivative powder, and the mass ratio of the organic solvent to the cellulose derivative is 500:1-1500:1;

[0021] The preparation method comprises placing the solution after adding the cellulose derivative on a magnetic heating stirrer at a temperature of 60° C.-100° C., mechanically stirring for 5-10 minutes, and rotating at a speed of 500-1000 rpm.

[0022] The second step comprises:

[0023] The particle size of the SAP particles is 0.5-1 mm, and the mass ratio of the SAP particles to the cellulose derivative is 1:2-1:1;

[0024] The preparation method comprises adding SAP to the solution described in step 1, and stirring the mixture in a magnetic heating stirrer at 60° C.-100° C. and 500-1000 rpm for 5-10 minutes.

[0025] The step three comprises:

[0026] The non-solvent is a substance such as petroleum ether or polyethylene that can be dissolved in an organic solvent and makes cellulose no longer soluble in the organic solvent, and the mass ratio of the non-solvent to the organic solvent is 1:50-1:25;

[0027] The preparation method comprises adding a non-solvent into the solution described in step 2, and stirring the solution in a magnetic heating stirrer at 60° C.-100° C. and 500-1000 rpm for 20-30 minutes.

[0028] The step 4 comprises:

[0029] The drying method is to put the SAP particles into an oven, set the drying temperature to 50±5° C., and dry until the mass measured twice before and after is less than 0.2% (the interval between the two mass measurements is 4 hours).

[0030] The step five comprises:

[0031] The alkaline activator is prepared by mixing water glass and solid sodium hydroxide, wherein the mass ratio of the water glass solution to the solid sodium hydroxide is 5:1-7:1;

[0032] The preparation method comprises the following steps: adding sodium hydroxide solid into water glass, mechanically stirring for 5-10 minutes, with the mechanical speed being 600-1000 rpm, obtaining a clear solution, and then sealing and standing the solution for more than 24 hours.

[0033] The step six comprises:

[0034] The foaming agent is a protein foaming agent, an ionic surfactant foaming agent, a vegetable oil foaming agent, etc.

[0035] The step seven comprises:

[0036] The mineral raw material is one or a mixture of metakaolin, fly ash and slag;

[0037] The mass ratio of the mineral raw material to the alkali activator is 1-2;

[0038] The preparation method is to add the alkali activator and the mineral raw material into a stirring pot at the same time and mechanically stir for 2-4 minutes at a rotation speed of 200-500 revolutions per minute.

[0039] The step eight comprises:

[0040] The mass ratio of the microencapsulated SAP to the total mass of the raw materials for preparing the geopolymer slurry is 1:500-1:100;

[0041] The mass ratio of the prefabricated foam to the total mass of the raw materials for preparing the geopolymer slurry is 1:20-1:10;

[0042] The preparation method comprises the following steps: adding microencapsulated SAP and prefabricated foam into a stirring pot containing geopolymer slurry, and mechanically stirring for 2-3 minutes at a rotation speed of 200-500 rpm.

[0043] The step nine comprises:

[0044] The curing time is 12-24 hours.

[0045] (III) Beneficial effects

[0046] The present invention utilizes SAP with delayed water absorption and release characteristics to modify the foam geopolymer, which has the following advantages compared with the prior art:

[0047] When SAP is added to foam geopolymer, it can improve chemical durability, frost resistance, and autogenous shrinkage;

[0048] The organic phase separation method is used to microencapsulate SAP with cellulose derivatives as the wall material, so that the water absorption-release time is delayed as a whole. After the slurry is poured, the SAP absorbs water from the geopolymer to avoid premature water absorption affecting the fluidity of the slurry during pouring. After the slurry is basically solidified, the SAP releases water to reduce the impact on the strength.

[0049] After dissolving, the cellulose derivative forms a gel to fill the microcracks inside the foam geopolymer, thereby improving the internal structure of the foam geopolymer;

[0050] The holes left after SAP releases water enhance the porosity of the foam geopolymer, thereby enhancing the sound absorption and heat insulation performance of the foam geopolymer. After SAP releases water, the foam geopolymer prepared by the present invention has higher strength than ordinary foam geopolymer under the same density. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The present invention is a process flow chart of a method for preparing a microencapsulated SAP-modified low-carbon foam geopolymer. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the specific embodiments of the present invention to clearly and completely describe the technical solutions in the specific embodiments of the present invention. Obviously, the specific embodiments described are only part of the specific embodiments of the present invention, not all of the specific embodiments. Based on the specific embodiments of the present invention, all other specific embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Embodiment 1:

[0054] (1) adding ethyl cellulose powder into xylene and stirring the mixture at 70° C. and 500 rpm for 5 minutes using a magnetic heating stirrer, wherein the mass ratio of ethyl cellulose to xylene is 1:1500;

[0055] (2) Adding SAP particles with a particle size of 0.5 mm to 1 mm into the solution and continuing stirring for 5 minutes, the mass ratio of SAP particles to ethyl cellulose is 1:2;

[0056] (3) Add polyethylene to the solution and continue stirring for 30 minutes to cause phase separation in the solution so that ethyl cellulose wraps around the SAP particles. The mass ratio of polyethylene to xylene is 1:50.

[0057] (4) After the solution is cooled, the SAP particles in the solution are filtered out and placed in an oven at a drying temperature of 50° C., and dried until the mass measured twice before and after is less than 0.2% (the interval between the two mass measurements is 4 hours) to obtain microencapsulated SAP;

[0058] (5) mixing water glass and solid sodium hydroxide solid and stirring to prepare an alkali activator, wherein the mass ratio of water glass to solid sodium hydroxide is 6.386:1;

[0059] (6) pouring the protein foaming agent into a foaming pot and connecting it to an air compressor, and using the air compressor to compress air to prepare prefabricated foam;

[0060] (7) mixing metakaolin and an alkali activator to prepare a geopolymer slurry, wherein the mass ratio of the metakaolin to the alkali activator is 1:1;

[0061] (8) adding microencapsulated SAP and prefabricated foam into geopolymer slurry and stirring at a speed of 200 rpm for 3 minutes to prepare microencapsulated SAP modified geopolymer slurry, wherein the mass ratios of microencapsulated SAP, prefabricated foam and the total mass of raw materials for preparing geopolymer slurry are 1:500 and 1:20, respectively;

[0062] (9) The microencapsulated SAP-modified low-carbon foamed geopolymer slurry is placed in a silicone mold and cured for 24 hours before demolding to obtain the final product.

[0063] Embodiment 2:

[0064] (1) adding methylcellulose powder to xylene and stirring the mixture at 60° C. and 600 rpm for 5 minutes using a magnetic heating stirrer, wherein the mass ratio of methylcellulose to xylene is 1:700;

[0065] (2) Adding SAP particles with a particle size of 0.5 mm to 1 mm into the solution and continuing stirring for 5 minutes, the mass ratio of SAP particles to methyl cellulose is 2:3;

[0066] (3) adding petroleum ether to the solution and continuing stirring for 30 minutes to cause phase separation in the solution so that the methylcellulose wraps around the SAP particles. The mass ratio of petroleum ether to xylene is 1:35.

[0067] (4) After the solution is cooled, the SAP particles in the solution are filtered out and placed in an oven at a drying temperature of 50° C., and dried until the mass measured twice before and after is less than 0.2% (the interval between the two mass measurements is 4 hours) to obtain microencapsulated SAP;

[0068] (5) mixing water glass and solid sodium hydroxide solid and stirring to prepare an alkali activator, wherein the mass ratio of water glass to solid sodium hydroxide is 5.3:1;

[0069] (6) pouring the vegetable oil foaming agent into a foaming pot and connecting it to an air compressor, and using the air compressor to compress air to prepare prefabricated foam;

[0070] (7) mixing fly ash and alkali activator to prepare geopolymer slurry, wherein the mass ratio of fly ash to alkali activator is 2:3;

[0071] (8) adding microencapsulated SAP and prefabricated foam into geopolymer slurry and stirring at a speed of 200 rpm for 3 minutes to prepare microencapsulated SAP modified geopolymer slurry, wherein the mass ratios of microencapsulated SAP, prefabricated foam and the total mass of raw materials of the prepared geopolymer slurry are 1:300 and 1:15, respectively;

[0072] (9) The microencapsulated SAP-modified low-carbon foamed geopolymer slurry is placed in a silicone mold and cured for 24 hours before demolding to obtain the final product.

[0073] Embodiment three:

[0074] (1) adding hydroxyethyl cellulose to carbon tetrachloride and stirring the mixture at 80° C. and 700 rpm for 5 minutes using a magnetic heating stirrer, wherein the mass ratio of hydroxyethyl cellulose to carbon tetrachloride is 1:500;

[0075] (2) Adding SAP particles with a particle size of 0.5 mm to 1 mm into the solution and continuing stirring for 5 minutes, the mass ratio of SAP particles to hydroxyethyl cellulose is 1:1;

[0076] (3) adding polyethylene to the solution and continuing stirring for 30 minutes to cause phase separation in the solution so that the hydroxyethyl cellulose wraps around the SAP particles. The mass ratio of polyethylene to carbon tetrachloride is 1:25.

[0077] (4) After the solution is cooled, the SAP particles in the solution are filtered out and placed in an oven at a drying temperature of 50° C., and dried until the mass measured twice before and after is less than 0.2% (the interval between the two mass measurements is 4 hours) to obtain microencapsulated SAP;

[0078] (5) mixing water glass and solid sodium hydroxide solid and stirring to prepare an alkali activator, wherein the mass ratio of water glass to solid sodium hydroxide is 5.3:1;

[0079] (6) pouring sodium lauryl sulfate foaming agent into a foaming pot and connecting it to an air compressor, and using the air compressor to compress air to prepare prefabricated foam;

[0080] (7) mixing the fly ash mixed with slag and an alkali activator to prepare a geopolymer slurry, wherein the mass ratio of the fly ash to the slag is 7:3, and the mass ratio of the total mass of the fly ash and the slag to the alkali activator is 1:2;

[0081] (8) adding microencapsulated SAP and prefabricated foam into geopolymer slurry and stirring at a speed of 200 rpm for 3 minutes to prepare microencapsulated SAP modified geopolymer slurry, wherein the mass ratios of microencapsulated SAP, prefabricated foam and the total mass of raw materials for preparing geopolymer slurry are 1:100 and 1:10, respectively;

[0082] (9) The microencapsulated SAP-modified low-carbon foamed geopolymer slurry is placed in a silicone mold and cured for 24 hours before demolding to obtain the final product.

[0083] Although specific embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the specific embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A microencapsulated SAP-modified low-carbon foam geopolymer and a preparation method thereof, characterized in that: The method comprises the following preparation steps: Step 1: adding cellulose derivative powder into an organic solvent and stirring at a certain temperature until the cellulose derivative powder is completely dissolved; Step 2: Add SAP particles into the solution in step 1 and stir evenly; Step 3: adding a non-solvent to the solution in step 2 and stirring, causing phase separation in the solution so that the cellulose derivative wraps around the SAP particles; Step 4: After the solution in step 3 is cooled, the SAP particles are filtered out and placed in an oven to evaporate the solvent to obtain microencapsulated SAP; Step 5: Mixing water glass and solid sodium hydroxide to prepare an alkali activator; Step 6: Pour the foaming agent into the foaming pot and connect the air compressor to prepare the prefabricated foam by compressing air with the air compressor; Step 7: Mixing the mineral raw material with the alkali activator described in step 5 to prepare a geopolymer slurry; Step 8: adding the microencapsulated SAP in step 4 and the prefabricated foam in step 6 to the geopolymer slurry in step 7 and stirring evenly; A microencapsulated SAP modified geopolymer slurry is obtained; Step nine: placing the microencapsulated SAP modified low-carbon foamed geopolymer slurry in step eight into a silicone mold, curing it, and then demoulding it to obtain the final product.

2. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step one comprises: The cellulose derivatives include methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, etc. The organic solvent is an organic substance such as xylene, carbon tetrachloride, cyclohexane, etc. that can dissolve cellulose derivative powder, and the mass ratio of the organic solvent to the cellulose derivative is 500:1-1500:1; The preparation method comprises placing the solution after adding the cellulose derivative on a magnetic heating stirrer at a temperature of 60° C.-100° C., mechanically stirring for 5-10 minutes, and rotating at a speed of 500-1000 rpm.

3. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The second step comprises: The particle size of the SAP particles is 0.5-1 mm, and the mass ratio of the SAP particles to the cellulose derivative is 1:2-1:1; The preparation method comprises adding SAP to the solution described in step 1, and stirring the mixture in a magnetic heating stirrer at 60° C.-100° C. and 500-1000 rpm for 5-10 minutes.

4. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step three comprises: The non-solvent is a substance such as petroleum ether or polyethylene that can be dissolved in an organic solvent and makes cellulose no longer soluble in the organic solvent, and the mass ratio of the non-solvent to the organic solvent is 1:50-1:25; The preparation method comprises adding a non-solvent into the solution described in step 2, and stirring the solution in a magnetic heating stirrer at 60° C.-100° C. and 500-1000 rpm for 20-30 minutes.

5. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step 4 comprises: The drying method is to put the SAP particles into an oven, set the drying temperature to 50±5° C., and dry until the mass measured twice before and after is less than 0.2% (the interval between the two mass measurements is 4 hours).

6. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step five comprises: The alkaline activator is prepared by mixing water glass and solid sodium hydroxide, wherein the mass ratio of the water glass solution to the solid sodium hydroxide is 5:1-7:1; The preparation method comprises the following steps: adding sodium hydroxide solid into water glass, mechanically stirring for 5-10 minutes, with the mechanical speed being 600-1000 rpm, obtaining a clear solution, and then sealing and standing the solution for more than 24 hours.

7. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step six comprises: The foaming agent is a protein foaming agent, an ionic surfactant foaming agent, etc.

8. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step seven comprises: The mineral raw material is one or a mixture of metakaolin, low-calcium fly ash, and steel slag; The mass ratio of the mineral raw material to the alkali activator is 1:1-2:1; The preparation method is to add the alkali activator and the mineral raw material into a stirring pot at the same time and mechanically stir for 2-4 minutes at a rotation speed of 200-500 rpm.

9. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step eight comprises: The mass ratio of the microencapsulated SAP to the total mass of the raw materials for preparing the geopolymer slurry is 1:20-1:10; The mass ratio of the prefabricated foam to the total mass of the raw materials for preparing the geopolymer slurry is 1:20-1:10; The preparation method comprises the steps of adding microencapsulated SAP and prefabricated foam into a stirring pot containing geopolymer slurry, and mechanically stirring the mixture for 2-3 minutes at a rotation speed of 200-500 rpm.

10. The microencapsulated SAP modified low-carbon foam geopolymer according to claim 1, characterized in that: The step nine comprises: The curing time is 12-24 hours.

Citation Information

Patent Citations

  • Low-shrinkage sludge ceramsite alkali-activated full-slag foam concrete plate and preparation method thereof

    CN104230280A

  • Efficient water-saving maintenance material

    CN112723788A

  • Steel slag-based anti-freezing geopolymer and preparation method thereof

    CN115784651A

  • Preparation method of Bayer process red mud-based geopolymer material system

    CN117700135A

  • Polymer microcapsule for self-repairing of ultra-high performance concrete and preparation method of polymer microcapsule

    CN118324437A